Early COVID-19 therapy with azithromycin plus nitazoxanide, ivermectin or hydroxychloroquine in outpatient settings significantly improved COVID-19 outcomes compared to known outcomes in untreated patients. (September 2021) - Cadegiani, F.A.; Goren, A.; Wambier, C.G.; McCoy, J.
Abstract: In a prospective observational study (pre-AndroCoV Trial), the use of nitazoxanide, ivermectin and hydroxychloroquine demonstrated unexpected improvements in COVID-19 outcomes when compared to untreated patients. The apparent yet likely positive results raised ethical concerns on the employment of further full placebo controlled studies in early-stage COVID-19. The present analysis aimed to elucidate, through a comparative analysis with two control groups, whether full placebo-control randomized clinical trials (RCTs) on early-stage COVID-19 are still ethically acceptable. The Active group (AG) consisted of patients enrolled in the Pre-AndroCoV-Trial (n = 585). Control Group 1 (CG1) consisted of a retrospectively obtained group of untreated patients of the same population (n = 137), and Control Group 2 (CG2) resulted from a precise prediction of clinical outcomes based on a thorough and structured review of indexed articles and official statements. Patients were matched for sex, age, comorbidities and disease severity at baseline. Compared to CG1 and CG2, AG showed reduction of 31.5–36.5% in viral shedding (p < 0.0001), 70–85% in disease duration (p < 0.0001), and 100% in respiratory complications, hospitalization, mechanical ventilation, deaths and post-COVID manifestations (p < 0.0001 for all). For every 1000 confirmed cases for COVID-19, at least 70 hospitalizations, 50 mechanical ventilations and five deaths were prevented. Benefits from the combination of early COVID-19 detection and early pharmacological approaches were consistent and overwhelming when compared to untreated groups, which, together with the well-established safety profile of the drug combinations tested in the Pre-AndroCoV Trial, precluded our study from continuing employing full placebo in early COVID-19. Highlights: Subjects with early COVID-19 treated with two-to-four drug combinations showed overwhelming improvements compared to untreated patients. Improvements remained massive even when underestimating benefits of proposed treatments and underestimating risks of non-treated COVID-19. Differences were sufficient to raise ethical concerns regarding the conduction of randomized clinical trials full-placebo in early COVID-19.